2017
DOI: 10.1038/s41598-017-12731-7
|View full text |Cite
|
Sign up to set email alerts
|

Glomalin contributed more to carbon, nutrients in deeper soils, and differently associated with climates and soil properties in vertical profiles

Abstract: Despite vital importance in soil conditioning and a proxy for arbuscular mycorrhizal (AMF), glomalin-related soil protein (GRSP) contribution to soil carbon and nutrients at vertical soil profiles and underlying mechanism were not well-defined yet. Thus, 360 soil samples were collected from 72 farmland 1-m soil profiles in northeastern China, and soil physiochemical properties, nutrients, glomalin characteristics, local climates were determined. Linear decreases of glomalin amounts were observed from the top t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 58 publications
9
50
1
1
Order By: Relevance
“…To extract glomalin-related soil protein (GRSP), soil samples from 5 replicates of each treatment (e.g., ICSC 1, 4, 7, 8, and 10) were randomly selected, dried at 50 • C for 24 h, and sieved (2.0 mm) prior to protein extraction following the protocol from Wright and Upadhyaya [39] with modification [40]. Easily extractable GRSP (EEG) was extracted from 0.5-g soil samples by adding 4 mL of 20 mmol L −1 sodium citrate (pH 7.0) solution followed by autoclaving at 121 • C for 30 min.…”
Section: Glomalin-related Soil Protein (Grsp) Extractionmentioning
confidence: 99%
“…To extract glomalin-related soil protein (GRSP), soil samples from 5 replicates of each treatment (e.g., ICSC 1, 4, 7, 8, and 10) were randomly selected, dried at 50 • C for 24 h, and sieved (2.0 mm) prior to protein extraction following the protocol from Wright and Upadhyaya [39] with modification [40]. Easily extractable GRSP (EEG) was extracted from 0.5-g soil samples by adding 4 mL of 20 mmol L −1 sodium citrate (pH 7.0) solution followed by autoclaving at 121 • C for 30 min.…”
Section: Glomalin-related Soil Protein (Grsp) Extractionmentioning
confidence: 99%
“…Urban forests management will greatly benefit from better understanding the relationships between microclimate regulation functions, urban forest structure, and local environmental conditions (Zhang et al 2013, Wang et al 2017b. Recent studies have demonstrated that higher trees have a better regulation capacity in terms of sunlight interception, air temperature and humidity (Giannico et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We have investigated most shelterbelt characteristics in this paper and parameters included tree size (height, DBH) and age, and community characteristics (tree density and shelterbelt width), as well as ditch width, depth, and distance to neighbouring farmlands. These latter parameters are particularly important for farmland productivity and in preventing nutrient and water losses (Wang et al 2017b). Both the RDA ordination and SEM analysis found insignificant effects on GRSP features (except for ditch width, as shown in the conditional term effects in the RDA ordination).…”
Section: Discussionmentioning
confidence: 89%